Facial Doppler ultrasound in minimally invasive procedures - Vidal Cofré, Natalia Francesca; Martinez, Victor Mercado; Novoa Cornejo, Ignacio (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Color Doppler ultrasound (US) is an important ally in minimally invasive aesthetic procedures at the facial level. The three-dimensional images obtained make it possible to carry out a complete vascular mapping of the face, relate the different anatomical structures and observe the cutaneous and subcutaneous thickness. Knowing this information will make it easier for the professional to carry out safe planning in the injection of a "filler" in different dermal structures. Thus, this article intends to be a guide when carrying out such procedures, as well as in the management of possible complications. Knowledge of this information will allow the professional a safer procedure, with fewer possibilities of complications and clinical failures, making aesthetic and functional results compatible satisfactorily.